Impacto das ações extensionistas do curso de licenciatura interdisciplinar em educação do campo no desenvolvimento educacional da cidade de Sumé/PB - Paiva, Regina Lemos (2022)
Historically, Brazilian society is marked by intense inequalities that generate exclusion processes in various areas of society. With regard to educational exclusion, rural people are a prominent group in this process, without greater opportunities for higher education. Universities in Brazil are based on the tripod of Teaching, Research and Extension, with the latter having the function of disseminating scientific knowledge with the external community, with Extension acquiring a great potential to transform social reality. This time, the promotion of training in higher education courses for the people of the countryside has been expressed through training policies at the intersection of social movements and universities. In this set is located the Degree Course in Rural Education of the Center for Sustainable Development of the Semi-Arid - CDSA, of the Federal University of Campina Grande - UFCG - Campus Sumé, with the objective of building training strategies from a relevant curricular organization to the reality of the people who live and work in the countryside. Based on this context, the present work has as a research question: What are the impacts produced by the extensionist actions of the Interdisciplinary Licentiate Course in Rural Education in the educational development of the city of Sumé/PB? The hypothesis that the impact produced by the Extension actions drives not only the university and society relationship, but also the educational development of the region constitutes the investigation and study guide from the theoretical categories of higher education, neoliberalism, university extension and development educational. Therefore, the general objective is to analyze educational development indicators to evaluate the impacts of the Extension actions promoted by the Interdisciplinary Licentiate Course in Rural Education - CDSA/UFCG in the city of Sumé/PB. To achieve the proposed objective, we took as a cut the mapping of the Extension actions from the years 2017 to 2020, under a qualitative approach of descriptive analysis and the methodological procedures of bibliographical and documental research. The study showed that, through university extension actions, the Rural Education course, at Campus Sumé/PB, enabled interaction between the university and society, fostering the process of knowledge creation, through the target audience of extension actions. , taking information to a less priority environment and benefiting the educational development of the region.